New records of leafhoppers and planthoppers from Austria (Hemiptera: Auchenorrhyncha) - Holzinger, Werner E. (Acta entomologica slovenica (Ljubljana), 2006)
New and interesting records of Auchenorrhyncha from Austria are presented. Five species are new to Austria: Delphacodes audrasi Ribaut, 1954, Florodelphax paryphasma (Flor, 1861), Alebra neglecta Wagner, 1940, Psammotettix sabulicola (Curtis, 1837) and Streptanus confinis (Reuter, 1880). Furthermore, 32 new records for Lower Austria, 9 for Carinthia, 3 for Styria, one for Salzburg and additional records of five interesting species are given. A synonymy published by Wagner (1961) is validated: Mocuellus Ribaut, 1946 is a synonym of Henschia Lethierry, 1892; Henschia collina (Boheman, 1850) comb. nov. is the correct name of Deltocephalus collinus Boheman, 1850 = Mocuellus collinus (Boheman, 1850).
Keywords: Austria; Avstrija; entomologija; favna; škržati